Translating Aristotelian Lexis in Euripides's Electra - Huffam, Ian (Université d'Ottawa / University of Ottawa, 2018)
In Poetics, Aristotle defines lexis as being the “language” of tragedy, and this language is one of the elements of tragedy that creates the mimetic representation. As Aristotle literally describes of the words of tragic composition as “doing” something, I consider lexis as an equivalent to J.L. Austin’s locutionary function of language, and the creation of the mimetic representation as the illocutionary. Aristotle’s conception of tragic composition requires a rigid understanding of the tragic form and its proper deployment as he leaves no room for perlocution, and so I also employ Jan Mukařovský’s theory of intentionality/unintentionality in art to explain how a play such as Euripides’s Electra may be understood as a product of the literary culture in which it arose. I then review historical trends of translating Greek tragedy into English to establish how modern translation is moving further away from reverence to the lexis of tragedy. Finally I address the various sections of Electra, a play with an almost non-existent performance record in English, to establish how I may respect the original lexis in my own translation, thereby imparting a (hopefully) similar effect on a modern audience.
Keywords: Tragedy; Euripides; Translation; Electra; Lexis; Aristotle; Mukarovsky; Extra-aesthetic